Risk factor profile of youth incarcerated for child to parent violence: A nationally representative sample. (September 2018) - Armstrong, Gaylene S.; Cain, Calli M.; Wylie, Lindsey E.; Muftić, Lisa R.; Bouffard, Leana A.
Abstract: Purpose: Intra-familial violence occurs in many forms yet few researchers examine child to parent violence (CPV), which occurs in almost 20% of single parent homes. Studies have neither developed a risk factor profile for youth involved in the most severe cases of CPV resulting in incarceration, nor included a comparison of gender-specific correlates. Methods: Data from the Survey of Youth in Residential Placement (SYRP) 2003, a large-scale, nationally representative sample of justice-involved youth between the ages of 10 and 20 who were survey using a multi-stage cluster sampling procedure is utilized. Results: Youth incarcerated for CPV are typically white and male. Youth, particularly female aggressors, tend to have substantial histories of substance use and/or victimization. Issues of mental health, poor school performance, and other maladaptive behaviors are also common. Conclusions: Relative concordance between CPV arrest and CPV incarceration risk profiles demonstrates youth who initially come into contact with law enforcement due to a report of CPV will continue and/or escalate the behaviors in a manner that will eventually result in arrest and out of home placement decisions. Interventions that focus on breaking the cycle of interfamilial violence thorough using collaborative, coordinated law enforcement and social services approaches are needed.